2001
DOI: 10.1210/en.142.8.3638
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Copper Zinc Superoxide Dismutase Impairs Human Trophoblast Cell Fusion and Differentiation

Abstract: The syncytiotrophoblast is the major component of the human placenta, involved in feto-maternal exchanges and secretion of pregnancy-specific hormones. Multinucleated syncytiotrophoblast arises from fusion of mononuclear cytotrophoblast cells. In trisomy 21-affected placentas, we recently have shown that there is a defect in syncytiotrophoblast formation and a decrease in the production of pregnancy-specific hormones. Due to the role of oxygen free radicals in trophoblast cell differentiation, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 51 publications
(67 reference statements)
1
30
0
2
Order By: Relevance
“…Abnormalities in chromosome 21 would seem to be an unlikely cause of our findings. Multiple studies have indicated that genetic abnormalities are a major cause of early pregnancy loss and spontaneous abortion (1)(2)(3)(33)(34)(35). Our data indicate that proportion of hCG-H is the cause, but we cannot totally exclude the possibility these findings could result from genetic abnormalities other than trisomy 21 that may limit hCG-H synthesis and alter cytotrophoblast cell metabolism.…”
Section: Sasaki Hcg-h and Pregnancy Failure Fertil Steril 2008mentioning
confidence: 59%
See 2 more Smart Citations
“…Abnormalities in chromosome 21 would seem to be an unlikely cause of our findings. Multiple studies have indicated that genetic abnormalities are a major cause of early pregnancy loss and spontaneous abortion (1)(2)(3)(33)(34)(35). Our data indicate that proportion of hCG-H is the cause, but we cannot totally exclude the possibility these findings could result from genetic abnormalities other than trisomy 21 that may limit hCG-H synthesis and alter cytotrophoblast cell metabolism.…”
Section: Sasaki Hcg-h and Pregnancy Failure Fertil Steril 2008mentioning
confidence: 59%
“…The possibility that hCG-H imbalance is an effect of genetic abnormalities modulating differentiation of the cytotrophoblast cells must be considered. We examined Down syndrome, or chromosome 21-related abnormalities, as the most common genetic abnormality and as the only disorder equated with hCG-H (33)(34)(35)(36). This genetic abnormality limits the differentiation of cytotrophoblasts to syncytiotrophoblasts, leading to a build up of cytotrophoblast cells (33)(34)(35)(36).…”
Section: Sasaki Hcg-h and Pregnancy Failure Fertil Steril 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to 9% O 2 impairs cell fusion and differentiation since desmoplakin and E-cadherin persist and a 70% decrease of hCG secretion was observed, suggesting cytotrophoblast aggregation without fusion (Alsat et al 1996). Impaired fusion and differentiation were also observed following overexpression of Cu/ZnSOD, a gene product of chromosome 21, in cytotrophoblasts (Frendo et al 2001). Interestingly, higher levels of Cu/ZnSOD mRNA, protein, as well as enzymatic activity were observed in trisomy 21-affected placentas, where there is a defect in syncytiotrophoblast formation and a decrease in the production of pregnancy-specific hormones.…”
Section: Trophoblast Fusion/differentiationmentioning
confidence: 99%
“…La concentration en ARN a été déterminée à 260 nm et leur intégrité a été vérifiée par électrophorèse sur gel d'agarose 1 %. Les niveaux de transcription de la β hCG ont été mesurés dans des homogénats placentaires totaux comme pré-cédemment décrit [15]. Le niveau des transcrits de la sialyltransférase-1 et de la fucosyl-tranférase-1 a été mesuré à partir des cellules en culture.…”
Section: Obtention Et Analyse Des Arnunclassified